Doping cobalt hydroxide nanowires for better supercapacitor performance. (1st February 2015) - Liu, Huajun; Ho, Kuan Hung; Hu, Yating; Ke, Qingqing; Mao, Lu; Zhang, Yu; Wang, John
Abstract: Cobalt hydroxide nanowires were synthesized on Ni foam by a one-pot hydrothermal process. The specific capacitance of pure cobalt hydroxide nanowires can reach ∼1600 F g −1 at a current density of 1 A g −1 . By suitably doping the redox-active element Mn into cobalt hydroxide nanowires, the specific capacitance is improved to ∼2800 F g −1 at 1 A g −1 . Doping with the redox-inactive elements La and Sr gives specific capacitances per cobalt mass of ∼245, ∼2200 and ∼3200 F g −1 at 1 A g −1 for La-doped, Sr-doped and La–Sr-doped cobalt hydroxides, respectively. The effect of doping is clarified in terms of the modifications caused to the morphology, oxidation state of cobalt, electronic conductivity and additional redox reactions of cobalt hydroxide. Our work shows that chemical doping is an effective and simple route to improve the supercapacitor performance of transition metal hydroxides.